Efficacy of Mesh Use in Breast Surgery: A Comprehensive Review of Complications and Aesthetic Outcomes - Sonya Williams, BS; Orr Shauly, MD; Ambika Menon, MD; Eliana Jolkovsky, BA; Daniel J. Gould, MD, PhD; Albert Losken, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The insertion of a mesh “internal bra” has been used in cosmetic breast procedures for soft-tissue reinforcement as a means to mitigate postoperative ptosis. However, there have been concerns regarding complications as a result of mesh placement and a lack of quantitative data regarding postoperative cosmetic outcomes. Methods:. Articles that assessed the effects of the mesh internal bra for soft-tissue support on cosmetic and patient-reported outcomes, complications, and surveillance were reviewed. Meta-analysis was performed to determine the overall complication rates, and cosmetic outcomes and patient-reported outcomes were reviewed. Results:. Meta-analysis showed the following summary effect sizes: infection/abscess had a pooled rate of 3.61% (Q = 33.8, I2 = 76.33%), hematoma was 1.34% (Q = 4.16, I2 = 68.1%), seroma was 5.04% (Q = 14.8, I2 = 73.11%), fat necrosis was 0.86% (Q = 693, I2 = 99.7%), and capsular contracture was 2.5% (Q = 693.4, I2 = 99.6%). Only 2 of 5 studies attempting to quantify cosmetic outcomes compared outcomes between patients who underwent procedures with and without the use of mesh. Both reported smaller increases in sternal notch-to-nipple distance and nipple-to-inframammary fold distance without clear statistical significance. Conclusions:. Although there does not seem to be a significant difference in risk profile with and without the use of mesh, the current data do not support the claims of improved cosmetic outcomes. Well-controlled, quantitative studies are necessary to objectively evaluate the cosmetic benefits of using mesh.